80 years later: Marine sediments still influenced by an old war ship - Van Landuyt, Josefien; Kundu, Kankana; Van Haelst, Sven; Neyts, Marijke; Parmentier, Koen; De Rijcke, Maarten; Boon, Nico (Frontiers in Marine Science, 2022)
Historic shipwrecks form an anthropogenic landmark in marine environment, yet their influence on the local geochemistry and microbiology remains largely unexplored. In this study, sediment and steel hull samples were taken around the V-1302 John Mahn, a World War II shipwreck, at increasing distance from the wreck, in different directions. Polycyclic aromatic hydrocarbons (PAH’s), explosives, and heavy metal levels were determined and related to the microbial composition. Benz(a)anthracene and fluoranthene remain present at the mg kg-1 level, probably originating from the coal bunker. These PAH’s indicate that the wreck is still influencing the surrounding sediments however the effects are very dependent on which side of the wreck is being studied. Known PAH degrading taxa like Rhodobacteraceae and Chromatiaceae were more abundant in samples with high aromatic pollutant content. Moreover, sulphate reducing bacteria (such as Desulfobulbia), proven to be involved in steel corrosion, were found present in the biofilm. This study shows that even after 80 years, a historic shipwreck can still significantly steer the surrounding sediment chemistry and microbial ecology.